Developing extensive reading supplementary materials for XI grad students at madrasah - Mia Midianti Nurmalia; Widyastuti Purbani (LingTera, 2018)
This research aimed to develop reading supplementary materials and to verify the appropriateness of the materials to support the learning process of the grade XI students at Madrasah Aliyah Al Ma’Had An-Nur. This research was a research and development study. The results of the research are as follows. First, this research produced a set of extensive reading supplementary materials. Second, the results of material validation by material and graphic designer experts, the try-outs by grade XI students, and the perception of the English teacher showed that the extensive reading supplementary materials were considered appropriate to be applied in English class.